2007
DOI: 10.2166/wst.2007.167
|View full text |Cite
|
Sign up to set email alerts
|

Odourous algal-derived alkenes: differences in stability and treatment responses in drinking water

Abstract: Drinking water supplies are often impacted by taste and odour (T/O) episodes caused by algal volatile organic compounds (AVOCs) from algal blooms. Treatment and control of these events is important to utility operators, as customer confidence in the safety of public drinking water supplies is based primarily on their palatability and odour. To manage T/O outbreaks successfully, knowledge about treatment responses of AVOCs and anticipation of their outbreaks are thus of major importance to the water industry. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
1
17
1
Order By: Relevance
“…Twenty milliliters of raw lake water was filtered through a GF/A glass filter; then, 10 ml of this raw water and the resulting filtrate were used for the subsequent analyses. The samples were placed in a headspace septum vial containing 4 g NaCl (12). After an internal-standard solution (10 l) of geosmin-D 3 was added, the vial was sealed with a Teflon-lined cap and then gently agitated to dissolve the salt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty milliliters of raw lake water was filtered through a GF/A glass filter; then, 10 ml of this raw water and the resulting filtrate were used for the subsequent analyses. The samples were placed in a headspace septum vial containing 4 g NaCl (12). After an internal-standard solution (10 l) of geosmin-D 3 was added, the vial was sealed with a Teflon-lined cap and then gently agitated to dissolve the salt.…”
Section: Methodsmentioning
confidence: 99%
“…Cyanobacteria produce numerous volatile organic compounds (VOCs), such as ␤-cyclocitral, geosmin, and 2-methylisoborneol (2-MIB) (10)(11)(12)(13). These volatile compounds have been shown to possess lytic activity against cyanobacteria (14).…”
mentioning
confidence: 99%
“…There was an outbreak of Dinobryon in Yinchuan at a cell intensity of 5.7 Â 10 4 cells/mL, which was one order of magnitude higher than its CDC value. Previous studies have reported that Dinobryon is likely to be more abundant at low temperatures (Naumenko, 1992;Agbeti and Smol, 1995) and accompanied with the occurrence of significant fishy odors (Rashash et al, 1995;Watson et al, 2001;Satchwill et al, 2007;Zhao et al, 2013). Thus, the strong fishy odor in Yinchuan could be associated with the abnormal growth of Dinobryon.…”
Section: Algal Population Characteristicsmentioning
confidence: 95%
“…6G-J; Watson et al, 2001a). Similar-sized blooms of these taxa in a large drinking water reservoir (Glenmore Reservoir, Alberta) had very different impacts on the treated water supplies (Watson and Satchwill, 2003;Satchwill et al, 2007). For example, blooms of the colonial chrysophyte Uroglena americana cause numerous T&O events in waters with low to moderate and severe eutrophication (Yano et al, 1988;Watson et al, 1996).…”
Section: Types Of Odors I Fishy/rancid/oily/cucumber and Floral Odorsmentioning
confidence: 99%